Using Artificial Neural Networks (ANN) to Control Chaos - Ighneiwa, Ibrahim; Hamidatou, Salwa; Ben Ismael, Fadia (Libyan Journal for Engineering Research, 2017)
Controlling Chaos could be a big factor in getting great stable amounts of energy out of small amounts of not necessarily stable resources. By definition, Chaos is getting huge changes in the system’s output due to unpredictable small changes in initial conditions, and that means we could take advantage of this fact and select the proper control system to manipulate system's initial conditions and inputs in general and get some desirable outputs out of undesirable Chaos. In this work,Artificial Neural Networks (ANN) techniques were used to get a desirable output out of otherwise a Chaotic system. Thatwasaccomplishedby first building some known chaotic circuit (Chua circuit) and then NI's MultiSim was used to simulate the ANN control system. It was shown that thistechnique can also be used to stabilize some hard to stabilize electronic systems.